PROBLEM SOLVING IN THE ARMY IS THE BASIS SOLUTIONS TO SOFTWARE PROBLEMS MORAL AND PSYCHOLOGICAL TRAINING MILITARY SERVICE IN SCHOOLS (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the moral and psychological training of youth for military service.